Effect of Training, Performance, and Work Motivation on Teacher Performance: A Narrative Review - Sa'ajiz, Muhammad; Hafiza (IJOSMAS, 2023)
Teacher performance is the work achieved by a teacher in carrying out their duties in accordance with the responsibilities given to them. However, based on facts on the ground, teacher performance is still not optimal. Work motivation is one of the factors that influence performance. Work motivation is also a requirement that is used by someone to do a job. In improving teacher performance, of course, it cannot be separated from encouragement from oneself or from outside, one of which is the principal as encouragement from outside. And work discipline is one factor that is no less important than work motivation. So that discipline is very important for the growth of an institution and organization to encourage its members to fulfill the demands of various predetermined provisions.